P.091 Consensus Guidelines for Utilization and Monitoring of Intravenous Immunoglobulin for Central Nervous System Disorders in British Columbia. (November 2021) - Uy, CE; Cross, HM; Percy, J; Schrader, D; Carruthers, R; Traboulsee, A; Beauchamp, A; Shih, AW; Morrison, D; Chapman, KM; Beadon, K
Abstract : Background: Intravenous immunoglobulin (IVIG) may benefit many inflammatory central nervous system (CNS) disorders based on multiple immunomodulatory effects. IVIG is being used in inflammatory CNS conditions however robust evidence and guidelines are lacking in many disorders. Over the last 5 years, the percentage of IVIG used for CNS indications within neurology almost doubled in British Columbia (BC), Canada. Clear local guidelines may guide rational use. Methods: Consensus guidelines for IVIG use for CNS indications were developed by a panel of subspecialty neurologists and the Provincial Blood Coordinating Office, informed by focused literature review. Guidelines were structured similarly to existing BC peripheral nervous system guidelines and Australian Consensus Guidelines. Utilization and efficacy will be monitored provincewide on an ongoing basis. Results: Categories of conditions for Possible Indication (N=11) and Exceptional Circumstance Use (N=4) were created based on level of evidence for efficacy. Dosing and monitoring recommendations were made and outcomes measures defined. Rationale for Not Indicated conditions (N=3) was included. Guidelines will be distributed to BC neurologists for feedback and re-evaluated after 1 year. Conclusions: IVIG use in CNS inflammatory conditions has an emerging role. Guidelines for use and monitoring of outcomes will help improve resource utilization and provide further evidence regarding effectiveness.